Primordialism and the 'Pleistocene San' of southern Africa. (19th July 2016) - Pargeter, Justin; MacKay, Alex; Mitchell, Peter; Shea, John; Stewart, Brian A.
Abstract: Abstract : Analogies are an important tool of archaeological reasoning. The Kalahari San are frequently depicted in introductory texts as archetypal, mobile hunter-gatherers, and they have influenced approaches to archaeological, genetic and linguistic research. But is this analogy fundamentally flawed? Recent arguments have linked the San populations of southern Africa with the late Pleistocene Later Stone Age ( c. 44 kya) at Border Cave, South Africa. The authors argue that these and other claims for the Pleistocene antiquity of modern-day cultures arise from a fundamental misunderstanding of the nature of cultural and archaeological taxonomies, and that they are a misuse of analogical reasoning.